Hydration status and fluid intake of young athletes from different sports during training - Bayram Ceylan (Türk Spor ve Egzersiz Dergisi)
Despite many studies presenting that a high number of adult athletes start exercise in sub-optimal hydration state, limited data concerning hydration levels in athletic youth exists. This study aimed to identify the hydration status of young athletes of different sports during a typical training. Sixty-nine young men athletes from different sports (swimming, judo, basketball, football) voluntarily participated in the study (age: 13.7±1.7 years, experience: 4.8±2.0 years). Measurements were carried out before and immediately after training. Data collection took place at the same time of the day. All athletes trained for about 90 minutes and they consumed fluids ad libitum during their training. Pre-training urine measurement revealed that 58.2% of the athletes started training in dehydrated state (USG≥1.020). Besides, 63.3% of the athletes completed the training in also dehydrated state with USG values ≥ 1.020 and urine colour between 4-6. Mean body weight loss during the training was -0.26±0.40. This study concluded that the prevalence of dehydration in young athletes is high according to USG and urine colour values. Great number of the athletes arrived at training in dehydrated state and dehydrated even more during training despite access to fluids. Some educational programs and measures for optimal hydration in young athletes should be taken into consideration.